Effective Strategic Management Planning and Control For A Manager - Nugraha, Agung Setya; Sihombing, Septian Oloan; Siahaan, Nur Halimah; Hakim, Abdul; Riyanti, Agustina; Bambang Setyobudi, (CARE: Journal Pengabdian Multi Disiplin, 2024)
This activity was carried out for students at Putra Bangsa University in Kebumen, Central Java. This community service aims to provide students with an understanding of the work of a professional manager which is carried out in four stages, namely planning, organizing, implementing, and controlling. The methods used in this community service activity are presentations and discussions. The results of the service show that the community service program for Putra Bangsa University students can be implemented well and run smoothly according to the activity plan that has been prepared. The results of this service can be concluded: First, students can combine practical experience in the workplace. Secondly, students can practically understand planning in the manufacturing, government, and hospital sectors. third, students can improve communication both theoretically and practically